THE PROBLEM OF FORMATION OF LANGUAGE AND SPEECH COMPETENCE OF PROFILE CLASS STUDENTS (Pedagogy of Higher and Secondary Education, 2011)
The article deacribes the problem of formation of speech compenetce on Ukrainian language lessons for students specialized classes, describes the basic issues of the researches: speech, competence, speech competence, communicative competence.
Keywords: language and verbal competence; communicative competence; professional competence